Consumer reactions to pay‐what‐you‐want and name‐your‐own‐price mechanisms. Issue 4 (5th January 2022) - Wagner, Rafael Luis; Pacheco, Natalia Araujo; Basso, Kenny; Rech, Eduardo; Pinto, Diego Costa
Abstract: Pay‐what‐you‐want (PWYW) and name‐your‐own‐price (NYOP) participative pricing mechanisms are becoming more popular among firms. In response, researchers have examined separate outcomes for each mechanism. However, questions remain, especially regarding which mechanism is most beneficial for consumers and companies. Therefore, our main objective is to investigate the role of these participative pricing mechanisms on consumers' pricing satisfaction, pain of payment, and amount of money they intend to pay. We also explore perceived control as mediating the effect of pricing mechanism on pricing satisfaction and pain of payment. Results from two experimental studies indicate that consumers are more satisfied with the pricing mechanism and feel less pain of payment under PWYW offers rather than under NYOP offers, but they intend to pay less than they would have paid for NYOP. External reference prices (ERPs) act as a boundary condition. That is, in both PWYW and NYOP pricing conditions, when retailers use ERPs, consumers intend to pay more but they are less satisfied with pricing and feel more pain of payment. The article concludes with implications for retailers using participative pricing.